Analysis Of Cash Ratio, Return on Assets, Debt to Equity Ratio and Earnings per Share Of Cash Dividend (Studies in Food and Beverage Subsector Company Listed in Indonesia Stock Exchange - Saraswati, Nungki Asri; Herawati, Juni (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study aims to examine and analyze the effect of the cash ratio, return on assets, debt to equity ratio and earnings per share of the cash dividend on food and beverage companies listed in Indonesia Stock Exchange. Secondary data were obtained from the annual financial statements in the Indonesia Stock Exchange. The population in this study amounted to 21 food and beverage companies listed in Indonesia Stock Exchange in 2010-2013. The sampling method used is saturated sampling method. The samples studied a total of 11 companies. Based on the hypothesis testing is done using multiple regression, the results showed that independent variable return on assets and earnings per share cash dividend significantly influence the food and beverage companies listed in Indonesia Stock Exchange. Keywords: Cash Ratio, Return on Assets, Debt to Equity Ratio, Earning per Share, Cash Dividend